Kesediaan atlit universiti terhadap kerjaya usahawan industri sukan - Asiah Mohd Pilus; Rosli Saadan (Centre for Languages and Human Development (UTEM), 2012)
This study aims to determine the elements of readiness among the university athletes in venturing into the sports industry entrepreneurship as a career option. The aspects of study include elements of attitude, knowledge and skills related to the sports industry entrepreneurship. This descriptive study encompasses a case study which engages the university athletes of the sports excellence program and focused sports in higher learning institutions. The instrument of the study is a set of questionnaires with Likert scale. The reliability of the questionnaires were verified in a pilot study with university athletes. The analysis of the data was carried out using the SPSS software. The findings from the study reveal that the university athletes demonstrate the elements of readiness towards sports industry entrepreneurship. This study also highlights the demography of the university athletes who display readiness to adopt the entrepreneurship in the sports industry as a career path. In addition to positive attitudes, the university athletes also indicate that knowledge and skills are the required elements to reflect readiness to be a sports industry entrepreneur. Thus, this underlines the sports industry entrepreneurship courses for university athletes upon graduation as a preparation to venture into the sports industry entrepreneurship.